Dampak dari auditor quality, financial stability, dan financial target terhadap fraudulent financial reporting - Deasy Emalia; Pratana Puspa Midiastuty; Eddy Suranta; Rini Indriani (Penerbit Goodwood, 2020)
Purpose: This study aims to provide empirical evidence of the effect of auditor quality, financial stability, and financial targets on fraudulent financial reporting. Research methodology: This research was quantitative descriptive combining the Beneish M-Score and Springate's Model in predicting fraudulent financial reporting. The sample in this study was non-financial companies listed on the Indonesia Stock Exchange with an observation period of 2010-2018. The sampling technique was purposive sampling and 1120 observations were obtained. Data processing was done using SPSS version 22 with logistic regression. Results: The results of the study prove that the auditor quality variable has a probability of a negative effect on FFR where the companies audited by BIG4 are able to minimize fraudulent financial reporting. Financial targets have negative effect on FFR, which means the lower the financial target, the greater the probability of the company to do fraudulent financial reporting. While the financial stability variable is negatively expected influencing the fraudulent financial reporting variable. Limitations: This study only used a sample of non-financial companies listed on the Indonesia Stock Exchange in 2010-2018 and met the criteria. The dependent variable fraudulent financial reporting was measured by the Beneish M-Score model and the Springate’s Model. The independent variable was auditor quality, financial stability, and financial target. Contribution: This research is expected to be able to enrich the literature and references that can be used as a reference in other studies as well as in the company. The results of this study are expected to provide a deeper understanding of how to predict fraudulent financial reporting using the Beneish M-Score and Springate’s Model. Keywords: Financial reporting, Auditor quality, Financial stability, Financial target